Towards Universal Accessibility: Architectural Barriers in Ukhrul, a Hilly District of Manipur - S. U. Priyanka; Joy Singh Akoijam; Longjam Nilachandra Singh; Monica Moirangthem; Shruti Pandey; Mongjam Anganba Khumancha (Indian Journal of Physical Medicine & Rehabilitation)
Introduction: Architectural barriers significantly impede access and mobility, especially for persons with disabilities (PWDs). Rural areas like Ukhrul, a hilly district in Manipur, face unique challenges in creating accessible environments due to their geographical constraints. This study aims to identify and evaluate these barriers in Ukhrul, their impact on accessibility for PWD and to address the need for effective solutions to eliminate mobility limitations. Materials and Methods: A descriptive and cross-sectional study was conducted from April to June 2024, assessing 50 buildings in Hungphung village, Ukhrul. The study included residential areas, public buildings and community spaces. A standardised accessibility checklist, based on national and international guidelines, was used. Researcher independently assessed each site, documenting architectural features such as ramps, signage, parking, doorways, thresholds, lifts, toilets and other necessary amenities. Data were analysed in percentage form to quantify the prevalence of various barriers. Results: The study revealed that only 12% of buildings met basic accessibility standards. Major barriers included the absence of ramps (76%), inaccessible toilets (82%), lack of signage (94%), inadequate doorway width for wheelchair (68%), inaccessible parking (87%), problematic thresholds (79%), railings (75%), inaccessible corridors (73%), windows (78%), stairways (81%) and absence of lifts (95%). These barriers severely hinder independent navigation and community participation for PWD. Discussion: This study highlights a significant gap in accessibility within Ukhrul. The lack of essential features such as ramps and toilets, along with insufficient signage poses major obstacles for PWD. This indicates a need for targeted infrastructure improvements and inclusive design strategies to enhance accessibility and support independence. Conclusion: This study underscores the critical need for comprehensive design improvements in Ukhrul to enhance accessibility for PWDs. Addressing these barriers through universal design principles will foster a more inclusive environment, allowing persons to navigate and participate fully in the community.